Shèng Nǚ: Stereotip Perempuan Lajang di China Pada Film “The Last Woman Standing” - Hervita Thalia Pratiwi R; Intan Erwani (Prodi Sosiologi FISIP ULM, 2023)
China is a country with a strong patriarchal culture and weakens the position of women, so that when women rebel and dare to fight against standards in society, they will be faced with stereotypes and discrimination. This research aims to know the forms of stereotypes experienced by Chinese women in the current era due to the mismatch between their attitudes or life choices and the norms that apply in society. This research examines the stereotypes experienced by single women in China to get the label Shèng Nǚ. The data source for this research is the film “The Last Woman Standing”, as well as other research supporting data sources. The research was conducted using qualitative descriptive methods. The theory used to analyze the research results is existential feminism from Beauvoir (1956). This research found stereotypical forms of single women in China shown in the film